Retention ideas for middle school piano students using group instruction - Pickering, Melinda (Kansas State University, 2016)
Maintaining interest to continue studying and practicing the piano during the middle school years can be very challenging. Not only are students distracted by so many activities but peer interactions and opinions are taken more seriously. One way to motivate piano students to continue study is to use some form of group instruction. This can be done in various ways, including theory and performance classes as well as chamber and duet preparations. I conducted two separate assessments: five middle-school aged boys and two sixth graders, a girl and a boy. I gave each of these participants a survey to determine the positive and negative outcomes experienced during these group experiences. The results of this study included the following conclusions: Students who take ownership of their music-making are also more motivated to practice; if they really enjoy a piece, they will learn it. This motivation also extends to playing with a friend, since the student will want to play competently in front of their friend. Extrinsic motivation (i.e. candy, prizes, etc.) is exciting at first, but does not really provide long-term motivation for the middle school student to practice more. The ensuing embarrassment of being unprepared was a stronger form of motivation. Middle school students also liked having goals such as working toward an upcoming festival or competition, since it gave them a goal toward which to work, even if they did not like the idea of being judged. Students also enjoyed playing duets with a parent, which proved to be a positive experience in this study. Occasionally, however, the teacher had to deal with factors beyond their control and the student decided to discontinue study.
Keywords: Retention; Middle School; Piano; Students; Group